THE MINIMAL SET OF INTERMOLECULAR INTERACTIONS IN THE STRUCTURES OF SUBSTITUTED PROLINES - BANARU, Alexander; KOCHNEV, Alexander (Studia Universitatis Babeș-Bolyai Chemia, 2017)
In this paper, the calculation of intermolecular interaction energy based on Gavezzotti–Filippini semi-empirical method was performed for the series of substituted prolines. The initial structural data were mined from Cambridge Structural Database. The topology of each structure was analyzed with respect to a minimal generator set of the space group. It was shown that the least number of strong symmetrically independent interactions required to generate a crystal structure is likely to exceed the cardinality of a minimal generator set.